Physiological effects of bi-level high-flow nasal cannula in healthy individuals: a proof of concept trial - Huh, Jin Won; Seo, Woo Jung; Ahn, Jee Hwan; Lee, Su Yeon; Suh, Hee Jung; Seo, Ga Jin; Kim, Eun Young; Jang, Min Kyung; Lim, Chae-Man (Frontiers in Medicine, 2025)
BackgroundHigh-flow nasal cannula (HFNC) delivers a continuous, unidirectional high flow of oxygen (Uniflow) throughout the respiratory cycle. Despite its positive pressure effects in the nasopharynx, the persistent high flow during expiration imposes additional work of breathing and disrupts the patient’s neural respiratory cycle. We devised a bi-level high-flow system (Biflow) allowing separate flow rate adjustments for inspiration and expiration.MethodsWe conducted a randomized crossover pilot study which we included healthy volunteer at ASAN Medical Center (April 2021 to June 2021). The data of 12 healthy volunteers (7 male, 5 female, average age 46.3 years) were analyzed. For Uniflow, flow settings of 30 (U30), 40 (U40), and 50 (U50) L/min were tested. In the Biflow, inspiratory flow rates were matched to the Uniflow settings, while expiratory flow rates varied from 10 to 30 L/min. The sequence of each flow (Uniflow vs. Biflow) was randomized and each flow setting was maintained for 3 min. Physiologic parameters, nasopharyngeal pressure-time product (N-PTP) as an energy cost proxy, end-expiratory lung impedance (EELI), and participant comfort were assessed.ResultsUniflow decreased respiratory rate and elongated expiratory time compared to natural breathing. However, these effects were less pronounced during Biflow. Compared with the Uniflow, both expiratory and inspiratory N-PTP were lower during the Biflow. Transcutaneous CO2 was lower during the Biflow compared with natural breathing or Uniflow. EELI did not differ between modes. All participants completed the study protocol without side effects.ConclusionIn healthy participants, compared with the conventional HFNC (Uniflow), Biflow showed less interference with the natural respiratory cycle of the participants. Compared with Uniflow, energy cost occurring in the nasopharynx was lower during BiflowClinical trial registrationhttp://cris.nih.go.kr/cris/, identifier KCT0006100.